Life-affirmation in Chirikure Chirikure's 'Europe Vakomana!' and Greater Mhondera's 'Usatye Kani Africa!'. Issue 2 (3rd July 2019) - Tembo, Charles; Mutasa, Dave
Abstract : Art that does not affirm life is invalid. Life-affirmation continues to be an urgent matter among peoples of Africa against the life-negating prison that European domination has located them in. The inspiration, impetus and ambition for African development require a consciousness of African history as centred people capable of unleashing their creative potential. In that regard, African literature is an indispensable tool to re-centre Africa. Against that background, this effort is a pursuit of the expression of 'life-affirmation' in selected Shona poetry in which indomitable determination towards reconstructing a new story about Africa and giving agency to African people are striking. That is, the poetry is redolent with a sharp sense of telling the African story against the long-standing and life-denying Eurocentric conceptualisations of Africa. The two poetic voices explicated in this article add to the many voices that are concerned with the critical need for Africa's 'mental bath' in the context of Euro-cultural imperialism. The voices are in concert with many other voices on the growing consciousness about Africa which is critical for self-transcendence. In the search for liberation from European resentment, self-knowledge and courage are presented as life-furthering and non-negotiable. The two poems, it is argued, are exemplars of African literature in search of renaissance.